The surfacing portion of the Iceberg of the Domestic Violence Phenomenon-data from the Israeli National Trauma Registry - Bella Savitsky; Irina Radomislensky; Sharon Goldman; Arielle Kaim; I. T. G. (Israel Trauma Group); Moran Bodas (BMC, 2021)
Abstract Background Domestic violence against women, which is an ancient phenomenon, is still thriving worldwide. The burden of domestic violence that is non-fatal on scene and its consequences in Israel are unknown. The purpose of this study was to provide evidence-based data regarding domestic violence-related hospitalizations among women in Israel. Methods The study is a retrospective cohort study of hospitalized patients included in the Israeli National Trauma Registry between January 1, 2011 and December 31, 2020. All women aged 14 and older, hospitalized due to a violence-related injury in one of the six-level I Trauma Centers or one of the 15 regional Trauma Centers in Israel were included (n = 676). Results Domestic violence contributes to moderate, severe, and critical injuries in a quarter of abused hospitalized women. Among these women, 20% underwent surgery, and in-hospital mortality was recorded for 2% of the patients. For most cases (53%), the spouse or ex-spouse caused the injury. The family relationship with the perpetrator was distributed differently between the population groups. The proportion of brothers who attacked sisters was greatest among Arabs (14.4%), while the phenomenon of attacking a mother was infrequent in the Arab sub-group. In contrast, among Jewish women, the proportion of those injured by a son was high, especially among the group of Jewish immigrants from the Former Soviet Union (FSU) (17%) and other countries (26%). In a multivariable logistic regression model with at least moderate injury as a dependent variable, in comparison to Israeli Arabs, Jews had a higher odds for sustaining at least moderate injuries, while the odds of Jewish immigrants not from FSU or Ethiopia were the highest (OR = 4.5, 95% CI 2.0-9.9). The annual hospitalization risk was 1.3/100,000 and 5.8/100,000, respectively for Jews and Arabs in 2020, almost fivefold higher among Arab women in comparison to Jewish women (RR = 4.6, 95% CI 2.9-7.3). Conclusions Domestic violence prevention should pay special attention to populations at risk, such as Arab women and new immigrants, as those women are especially vulnerable and often without sufficient family support and lack of economic resources to exit the trap of domestic violence. The collaboration between social and health services, the police, and the local authorities is crucial.